Cone Beam Computed Tomography in an Evaluation and Diagnosis of Anatomical Variations and Pathological Lesions in Maxillary Sinus Prior to Maxillary Sinus Lift Surgery - Zainab H Al-Ghurabi (College of Dentistry/ University of Baghdad, 2016)
Abstract: Thorough assessment of the Maxillary,Sinus is very important. Recently 3-dimensional imagewith Cone Beam Computed Tomography (CBCT) is very dependable in Maxillary Sinus diagnosis. The aim of this study is to: shade light on the role of (CBCT) diagnosis of the maxillary sinus anatomical variation and pathological finding among smokers and nonsmokers prior to maxillary sinus lift techniques. Materials and Method: In this study 60 males with age ranged between 20-50 years old, referred for (CBCT) assessment of maxillary sinus in the Specialist Health Center of AL-Sadder city. The scanning were performed using Kodak 9500 (CBCT), the KV was 90, mA10 and scanning time 10 s. Voxel size 0.3mm with( DICOM ) software on a multiplaner reconstruction window in which the axial, coronal and sagittal plane could be visualized in 0.3 mm interval, 40 were smokers and 20 nonsmokers, both sides were evaluated to assess the presence of septa, maxillary sinus membrane (Schneiderian membrane)thickening, complete opacification and adenoid polyp. Result:The maxillary for nonsmoker patients (20) patients were clean and have no any pathological or anatomical changes, among smoker patients, it was found that 7 (17.5%) of them had a clean maxillary sinus, 25 (62.5%) patient from smokers, the mucosal thickening was clear and measured more than 4 mm, 20 (80%) of them bilateral maxillary sinus were involved and 5 (20%) of them have a unilateral thickening, 6 (15%) of the smoker patient have bilateral involved adenoid with max sinus, and 2(5%) of them have full opacification., no septa was found in this study. Conclusion:Cone Beam Computed Tomography(CBCT)was themost useful technique to diagnose maxillary sinusbefore maxillary sinus augmentation, an evaluation ofCone Beam Computed Tomography(CBCT)scans before implant surgery or sinus augmentation procedures has extreme clinical importance in evaluation of anatomic structures, such as thickening of the Schneiderian membrane and presence of pathological lesion such as adenoid polyp. Key words: Cone beam computed tomography, maxillary sinus, anatomical variations.